Don't You Wish You Had Fused to the Pelvis the First Time: A Comparison of Reoperation Rate and Correction of Pelvic Obliquity. Issue 8 (15th April 2019) - Nielsen, Ena; Andras, Lindsay M.; Bellaire, Laura L.; Fletcher, Nicholas D.; Minkara, Anas; Vitale, Michael G.; Troy, Michael; Glotzbecker, Michael; Skaggs, David L.
Abstract : Study Design: A multicenter retrospective study. Objective: The aim of this study was to compare pelvic obliquity correction and reoperation rate in neuromuscular scoliosis patients who had their pelvis included in a posterior spinal fusion (pelvic fusion, PF) at their index procedure versus revision procedures. Summary of Background Data: There is limited information on outcomes specific to fusing to the pelvis for neuromuscular scoliosis in a revision operation versus index surgery. Methods: Charts and radiographs were reviewed of patients with PF for neuromuscular scoliosis from January 2003 to August 2015 at four high-volume pediatric spine centers with >2 year follow-up. Results: Two hundred eighty-five patients met inclusion criteria; 271 had PF done at index surgery and 14 had PF done during revision surgery. Before index procedure, there were no significant differences in Cobb angle ( P = 0.13). Before PF, there was no difference in pelvic obliquity ( P = 0.26). At the time of fusion to the pelvis, estimated blood loss ( P = 0.23) and operative time ( P = 0.43) did not differ between index and revision groups. Percent correction in pelvic obliquity was similar for both groups ( P = 0.72). Overall, 69 patients had complications requiring return to the operating room. Excluding the revision surgery for inclusion of the pelvis for the revision group, there was still a lower reoperation rate with index PF (22.9%, n = 62/271) than revision PF (50.0%, n = 7/14) ( P = 0.02). Implant failures were significantly higher in the revision group (index = 7.4%, 20/271; revision = 42.9%, 6/14; P < 0.001). Conclusion: PF at the index spinal fusion led to similar correction of pelvic obliquity with approximately half the reoperation rate compared with PF at a revision surgery. Operative time and blood loss were similar between index and revision spinal fusion. Level of Evidence: 4 Abstract : Pelvic fusion at index spinal fusionled to similar correction of pelvic obliquity with half the reoperation rate compared to PF at revision surgery. While we would intuitively think that extension to the pelvis is a relatively small procedure, operative time and blood loss were similar to the index fusion.